Crianças de seis anos no ensino fundamental: em foco a dimensão motora - Cintra, Fátima Bissoto Medeiros (2012)
This research aims to understand how motricity in six-year-old children has been handled in elementary school, considering that for Wallon theoretical reference for this study motricity is a synonym of psychomotricity, since he understands it as indissociable from psychism. The research had a qualitative approach and, for the production of information, observation sessions have been made, having a total of 23h35min, distributed in four consecutive weeks. Two 1st grade classes from a school in the West area of São Paulo have been observed, at different times, and with different teachers. The results of the observation have been recorded on a field journal. The information produced has been organized on a chart to facilitate analysis and discussion, raising four thematic axes: movement and teaching process, space and movement, movement and representation, and movement and mental self-discipline. This study has pointed out that schools do not still recognize the importance of motricity both for cognitive and affective development, even if today there are practices which integrate the movement to the activities performed. Schools do not recognize it is their job to offer opportunities for the six-year-old children to experience physical space which is fundamental for the construction of mental space , and they offer few moments for fictional play, which are important for the strengthening of representation